2018
DOI: 10.1163/15685381-20181102
|View full text |Cite
|
Sign up to set email alerts
|

X-ray microtomography in herpetological research: a review

Abstract: Herpetological research, like any other (palaeo)biological science, relies heavily on accurate data collection, particularly visualisation and quantification of anatomical features. While several high-resolution imaging methods are currently available, one technique in particular, x-ray microtomography or micro-computed tomography, is on the verge of revolutionising our understanding of the morphology of amphibians and reptiles. Here, we present a review on the prevalence and trends of x-ray microtomography in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 111 publications
0
17
0
Order By: Relevance
“…Although some digital morphology studies have included hundreds of 18 , 19 or over a thousand 20 23 3D models, their images are often aggregated using different sources (museums, repositories, laboratories), methods (surface scanning, μCT), and parameters (X-ray energy, voxel size, number of projections), making it difficult to integrate and compare findings. For smaller specimens in particular, variation in spatial resolution can result in significant measurement errors, for example in estimated volumes or relationships between traits 24 , 25 . Limitations on time and money for μCT scanning also mean that specimen data are often collected haphazardly, constraining systematic analyses to one or few individuals per species 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although some digital morphology studies have included hundreds of 18 , 19 or over a thousand 20 23 3D models, their images are often aggregated using different sources (museums, repositories, laboratories), methods (surface scanning, μCT), and parameters (X-ray energy, voxel size, number of projections), making it difficult to integrate and compare findings. For smaller specimens in particular, variation in spatial resolution can result in significant measurement errors, for example in estimated volumes or relationships between traits 24 , 25 . Limitations on time and money for μCT scanning also mean that specimen data are often collected haphazardly, constraining systematic analyses to one or few individuals per species 6 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the distribution of inclusions, fractures, internal defects, and impurities, as well as surface features of gems can be easily distinguished (Figure 1). Despite the high cost of µCT hardware, it is a technology used in a wide variety of applications such as geosciences [23][24][25], materials science [26], civil engineering materials [27], biological applications [28], herpetology [29], biomimicry [30] and additive manufacturing [31]. This broad application ability has resulted in increased availability in the form of service laboratories all over the world.…”
Section: X-ray Micro Computed Tomography (µCt)mentioning
confidence: 99%
“…Recent studies have focused on adult morphology and on descriptive aspects of biology of several species of living fishes 5 7 , salamanders 8 10 , caecilians 11 14 , frogs and toads 15 19 , lizards 20 22 , snakes 23 25 , amphisbaenians 26 28 , turtles 29 31 , crocodiles 32 34 , birds 35 37 , and mammals 38 40 , besides fossils of several vertebrate groups 41 , 42 . On herpetological research, studies that encompass developmental series, together with other purely anatomical studies, represents the most of works reported this way, mainly for anurans and squamates species 43 . However, in developmental studies, is still hard to obtaining complete (or almost) developmental series and/or to discriminate soft tissues (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if changes of a particular element were to be followed, and one wants, for instance, to follow the amount of bone deposition and ossification, and elaborate area reconstructions have been devised to account for that 52 . One of the advantages of microtomography reconstruction, and software developed for it (as for example, the software used herein; see below), is that volume and other sort of measurements can be performed 43 to selected tissues and organs.…”
Section: Introductionmentioning
confidence: 99%